Layered zinc hydroxide monolayers by hydrolysis of organozincs - Leung,AHM; Pike,SD; Clancy,AJ; Yau,HC; Lee,WJ; Orchard,KL; Shaffer,MSP; Williams,CK (CHEMICAL SCIENCE, 2018)
2D inorganic materials and their exfoliated counterparts are both of fundamental interest and relevant for applications including catalysis, electronics and sensing. Here, a new bottom-up synthesis route is used to prepare functionalised nanoplatelets, in apolar organic solvents, via the hydrolysis of organometallic reagents; the products can be prepared in high yield, at room temperature. In particular, a series of layered zinc hydroxides, coordinated by aliphatic carboxylate ligands, were produced by the hydrolysis of diethyl zinc and zinc carboxylate mixtures, optimally at a molar ratio of [COOR]/[Zn] = 0.6. Layered zinc hydroxides coordinated by oleate ligands form high concentration solutions of isolated monolayers (3 nm thick x ∼ 26 nm) in apolar organic solvents (up to 23 mg mL−1 in toluene), as confirmed by both atomic force and transmission electron microscopies of deposited species. The high solubility of the product allows the synthetic pathway to be monitored directly in situ through 1H NMR spectroscopy. The high solubility also provides a route to solution deposition of active functional materials, as illustrated by the formation of nanoporous films of optically transparent porous zinc oxide (1 μm thickness) after annealing at 500 °C. This new organometallic route to 2D materials obviates common complications of top-down exfoliation syntheses, including sonochemical-degradation and low yields of aggregated polydispersed layers, and may potentially be extended to a wide range of systems.